Our intelligent bodies - Merrill, Gary F. (Rutgers University Press, 2021)
Human intelligence isn't just located in the brain. Our bodies are marvelously sophisticated and complex, with a variety of autonomic systems that help maintain our health without us ever having to think about them. But how exactly do all these physiological structures actually work? In Our Intelligent Bodies, physiology professor Gary F. Merrill takes you on a guided tour through the human body. You'll learn how our eyes are designed to detect unimaginably small bursts of light and how our ears contain bundles of tiny hairs, each one attuned to different sound frequencies. You'll also discover how our hearts are smart enough to compensate for skipped beats and irregular rhythms and how our pulmonary system adjusts for low oxygen levels. You'll even find out why the gut is sometimes called the "second brain," its reflexes controlled by millions of neurons. Written in a fun, easy-to-comprehend style and filled with illuminating analogies, Our Intelligent Bodies also brings readers up to date on cutting-edge research into the wonders of human physiology. It will give you a new appreciation for the smart decisions our bodies are making when our brains aren't paying attention.